Development of Chloroplast and Nuclear DNA Markers for Chinese Oaks (Quercus Subgenus Quercus) and Assessment of Their Utility as DNA Barcodes - Yang, Jia; Vázquez, Lucía; Chen, Xiaodan; Li, Huimin; Zhang, Hao; Liu, Zhanlin; Zhao, Guifang (Frontiers in Plant Science, 2017)
Chloroplast DNA (cpDNA) is frequently used for species demography, evolution, and species discrimination of plants. However, the lack of efficient and universal markers often brings particular challenges for genetic studies across different plant groups. In this study, chloroplast genomes from two closely related species (Quercus rubra and Castanea mollissima) in Fagaceae were compared to explore universal cpDNA markers for the Chinese oak species in Quercus subgenus Quercus, a diverse species group without sufficient molecular differentiation. With the comparison, nine and 14 plastid markers were selected as barcoding and phylogeographic candidates for the Chinese oaks. Five (psbA-trnH, matK-trnK, ycf3-trnS, matK and ycf1) of the nine plastid candidate barcodes, with the addition of newly designed ITS and a single-copy nuclear gene (SAP), were then tested on 35 Chinese oak species employing four different barcoding approaches (genetic distance-, BLAST-, character- and tree-based methods). The four methods showed different species identification powers with character-based method performing the best. Of the seven barcodes tested, a barcoding gap was absent in all of them across the Chinese oaks, while ITS and psbA-trnH provided the highest species resolution (30.30%) with the character- and BLAST-based methods, respectively. The six-marker combination (psbA-trnH + matK-trnK + matK + ycf1 + ITS + SAP) showed the best species resolution (84.85%) using the character-based method for barcoding the Chinese oaks. The barcoding results provided additional implications for taxonomy of the Chinese oaks in subg. Quercus, basically identifying three major infrageneric clades among the Chinese oaks (corresponding to Groups Quercus, Cerris and Ilex) referenced to previous phylogenetic classification of Quercus. While the morphology-based allocations proposed for the Chinese oaks in subg. Quercus were challenged. A low variation rate of the chloroplast genome, and complex speciation patterns involving incomplete lineage sorting, interspecific hybridization and introgression, possibly have negative impacts on the species assignment and phylogeny of oak species.